2008
DOI: 10.1186/1471-2407-8-117
|View full text |Cite
|
Sign up to set email alerts
|

Association of common ATMvariants with familial breast cancer in a South American population

Abstract: Background: The ATM gene has been frequently involved in hereditary breast cancer as a lowpenetrance susceptibility gene but evidence regarding the role of ATM as a breast cancer susceptibility gene has been contradictory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 27 publications
0
36
2
Order By: Relevance
“…The ATM kinase has an essential role maintaining genomic integrity, as a key activator of cellular responses to DNA double-strand breaks [61]. In Chile and Mexico, association studies were performed to evaluate the relationship between common ATM variants and familial BC [62,63]. The same variants were studied in both countries: IVS24-9delT and IVS38-8T>C. Both reports concluded that these variants are associated with increased risk of BC (Table 5).…”
Section: Other Bc Susceptibility Mutations In Central and South Amerimentioning
confidence: 99%
“…The ATM kinase has an essential role maintaining genomic integrity, as a key activator of cellular responses to DNA double-strand breaks [61]. In Chile and Mexico, association studies were performed to evaluate the relationship between common ATM variants and familial BC [62,63]. The same variants were studied in both countries: IVS24-9delT and IVS38-8T>C. Both reports concluded that these variants are associated with increased risk of BC (Table 5).…”
Section: Other Bc Susceptibility Mutations In Central and South Amerimentioning
confidence: 99%
“…All of these were in heterozygous state, very similar to the results found in this study, indicating that being the carrier of one of these alleles alone or in combination may alter the risk for cancer, probably through increased genetic instability or through altering the normal response for DNA damage repair, as described previously. 10 Additionally, we found that haplotype T/(-T), TT, G/G appear to confer risk to BC (OR 3.41; CI 1.38-8.43); however, as can be seen in table I, in this case such risk should be attributable in fact to allele IVS24-9delT (T/-T).…”
Section: Discussionmentioning
confidence: 62%
“…10 For polymorphism 5557G>A, the authors described a heterozygous frequency of 20.6% in cases and of 13% in controls. Similar frequencies were found for the variant IVS24-9delT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations